Algeria : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
Owing to the implementation of IMF-supported programs in 1994-98, Algeria's macroeconomy has improved. In 1999, there was an upward trend in the agricultural sector. The hydrocarbon sector represents the main source of foreign exchange earnings. Revenue developments are particularly sensitive to changes in the world oil prices and exchange rate fluctuations. The monetary policy framework used by the monetary authority could be more explicit. Finally, a low level of inflation in the medium term has been attained. Algeria's tariffs ranges between 5 and 45 percent.